Selective fixation of the medial malleolus in unstable ankle fractures. Issue 4 (April 2019) - Carter, Thomas H.; Mackenzie, Samuel P.; Bell, Katrina R.; Hollyer, Marcus A.; Gill, Emma C.; MacDonald, Deborah J.; Duckworth, Andrew D.; White, Timothy O.
Highlights: Non-operative management of reduced medial malleolar fractures, following fibular fixation, does not appear to compromise outcome. Medial sided complications can be reduced, avoiding a 10% return to theatre rate for infection and metalwork removal. This study has prompted a prospective randomised controlled trial that aims to validate these retrospective findings. Abstract: Background: Whilst the lateral malleolus appears to be crucial in controlling anatomical reduction of the talus, the role of the medial malleolus is less clear. Medial sided complications including infection, damage to local structures and symptomatic hardware are not without morbidity. This study compares the outcomes of patients with bimalleolar or trimalleolar ankle fractures who underwent fibular nail stabilisation with or without medial malleolar fixation. Methods: From a prospective single-centre trauma database, we identified 342 patients over a nine-year period who underwent fibular nail insertion to stabilise a bimalleolar or trimalleolar ankle fracture. Isolated lateral malleolar fractures were excluded. Demographic data, clinical outcomes, radiographic evaluation, return to work and sport, and patient reported outcomes, including Olerud-Molander Ankle Score (OMAS), EuroQol-5D (EQ-5D) and Manchester-Oxford Foot Questionnaire (MOXFQ) were collected. Results: This study included 247 patients with a mean age of 66.7 years (range, 25–96 years), of whom 200 were female (81%). Medial malleolar fixation was not performed in 54 cases (22%). There was no significant difference between groups with respect to failure of fixation (p = 0.634) or loss of talar reduction (p = 0.157). No patient required surgery for a symptomatic medial malleolar non-union. Medial sided complications occurred in 32 (16%) of the fixation group, of whom 20 (10%) required further surgery. At a mean mid-term follow-up of 4.8 years (range, 8 months – 9 years) there was no significant difference between the non-fixation and fixation groups with respect to the median OMAS (85 vs 80; p = 0.885) or median EQ-5D (0.80 vs 0.81; p = 0.846). Patient satisfaction was not significantly different between the two groups (85/100 vs 87/100; p = 0.410). Conclusion: Non-operative management of the medial malleolar component of an unstable ankle fracture treated with a fibular nail may reduce the rate of post-operative complications without compromising the patient reported outcome.